PU.1 is required to restrain myelopoiesis during chronic inflammatory stress - Chavez, James S.; Rabe, Jennifer L.; Niño, Katia E.; Wells, Harrison H.; Gessner, Rachel L.; Mills, Taylor S.; Hernandez, Giovanny; Pietras, Eric M. (Frontiers in Cell and Developmental Biology, 2023)
Chronic inflammation is a common feature of aging and numerous diseases such as diabetes, obesity and autoimmune syndromes, and has been linked to the development of hematological malignancy. Blood-forming hematopoietic stem cells (HSC) can contribute to these diseases via production of tissue-damaging myeloid cells and/or acquisition of mutations in epigenetic and transcriptional regulators that initiate evolution toward leukemogenesis. We previously showed that the myeloid ‘master regulator’ transcription factor PU.1 is robustly induced in HSC by pro-inflammatory cytokines such as interleukin (IL)-1b and limits their proliferative activity via repression of protein synthesis and cell cycle activity. Here, we used a PU.1-deficient mouse model to investigate the broader role of PU.1 in regulating hematopoietic activity in response to chronic inflammatory challenge. We found that PU.1 serves a critical role in restraining inflammatory myelopoiesis via suppression of cell cycle and self-renewal gene programs in myeloid-biased multipotent progenitor (MPP) cells. Our data show that while PU.1 functions as a key driver of myeloid differentiation, it plays an equally critical role in tailoring hematopoietic responses to inflammatory stimuli while limiting expansion and self-renewal gene expression in MPPs. Taken together, these data identify PU.1 as a key regulator of inflammatory myelopoiesis with relevance to disease and leukemogenesis.